2015
DOI: 10.15640/ijgws.v3n1a2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Pathways to Delinquency: Exploring Associations between Familial Background, Traumatic Victimization and Violent Behavior among Urban Female Adolescents

Abstract: This paper discusses parental background and traumatic victimization as risk factors for violent delinquency among a sample of 208 urban adolescent females. Focus group and in-depth interviews conducted on a subsample of 20 participants are also presented, and emphasis is placed on the factors that place these female juveniles at a greater risk of engaging in delinquent behavior. Suggestions for future research are also addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…While it is widely known that African-American youths in these violent communities are at an increased risk for both internalizing and externalizing symptomatology, less is revealed about the level at which coping may serve as a buffer or mitigate the effects of levels of victimization in particular. Studies that have pointed toward the impact of direct and indirect victimization tend to include specific types of victimization as indicators of direct exposure, while fewer analyses have examined variations in coping strategies among the rates and type of violent victimization as part of a composite variable [5,6,7]. Moreover, research has shown that the coping strategies employed by minority youths can either increase or decrease their likelihood of engaging in delinquent behavior, and this relationship can be impacted by gender, age, and family structure.…”
Section: Introductionmentioning
confidence: 99%
“…While it is widely known that African-American youths in these violent communities are at an increased risk for both internalizing and externalizing symptomatology, less is revealed about the level at which coping may serve as a buffer or mitigate the effects of levels of victimization in particular. Studies that have pointed toward the impact of direct and indirect victimization tend to include specific types of victimization as indicators of direct exposure, while fewer analyses have examined variations in coping strategies among the rates and type of violent victimization as part of a composite variable [5,6,7]. Moreover, research has shown that the coping strategies employed by minority youths can either increase or decrease their likelihood of engaging in delinquent behavior, and this relationship can be impacted by gender, age, and family structure.…”
Section: Introductionmentioning
confidence: 99%